2021
DOI: 10.1002/rfe.1141
|View full text |Cite
|
Sign up to set email alerts
|

CEO gender and corporate labor cost

Abstract: We examine the impact of CEO gender on firm‐level average labor cost. In a sample of U.S. public firms with voluntary labor cost disclosure, we find that firms with female CEOs have significantly lower average labor cost than firms with male CEOs. This effect is robust to the use of propensity score matching approach to alleviate the impact of possible selection bias and endogeneity concerns. The results are stronger in a subsample of firms where CEO turnover introduces CEO gender change. We hypothesize that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
(88 reference statements)
1
5
0
Order By: Relevance
“…Barber and Odean (2001) find that married individuals have (1) a higher propensity to invest than single men and (2) exhibit less portfolio turnover, resulting in more positive long‐term investment outcomes. Similarly, Fan et al (2021) find that female CEOs tend to pursue less risky corporate policies, suggesting the impact from married men is driving this result (CEOs are most often men during our sample period). Bertocchi et al (2011) find that married individuals are more likely to invest in riskier assets due to social benefits provided by the marriage relationship.…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 69%
“…Barber and Odean (2001) find that married individuals have (1) a higher propensity to invest than single men and (2) exhibit less portfolio turnover, resulting in more positive long‐term investment outcomes. Similarly, Fan et al (2021) find that female CEOs tend to pursue less risky corporate policies, suggesting the impact from married men is driving this result (CEOs are most often men during our sample period). Bertocchi et al (2011) find that married individuals are more likely to invest in riskier assets due to social benefits provided by the marriage relationship.…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 69%
“…In addition, from a sample of Fortune 500 companies, Erhardt et al (2003) concluded that company profitability is related to the number of female managers: the higher the number, the more profitable the company is compared with the industry average. In addition, a sample of US public firms showed a positive relationship between female CEOs and firm performance; female CEOs contribute to lower labor costs and thus higher firm performance and are more likely to be hired at times of poor performance (Fan et al , 2021). However, a sample of Indian companies suggested that CEO gender does not have a significant effect on firm performance, possibly because of the rarity of female CEOs in such firms (Kaur and Singh, 2018).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Existing studies provide mixed results about the impact of female executives on employee salaries. Some studies found that female executives have a negative impact on employee salary (Fan et al, 2021;Gagliarducci and Paserman, 2015). However, existing research suggests that female executives may have a positive effect on employee salaries.…”
Section: Theoretical Underpinning and Hypothesesmentioning
confidence: 99%
“…One is that, a distinguishing feature of the reward system in China is high and varied benefits instead of high salary (Lin et al, 2014). Fan et al (2021) found that firms with female CEOs have lower average labor costs but offer higher non-monetary employee benefits, especially in human capital-intensive firms. The other explanation is that female executives are usually more prudent and traditional than male executives regarding financial matters, and they are typically more risk-averse in making decisions (Carter et al, 2017).…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation